STUDENT RESPONSE ANALYSIS OF THE LEARNING PPKN HIGH SCHOOL CLASS X USES ENCYCLOPEDIA ARCHIPELAGOS - Wahyu Agung Fauzi Zakaria; Ida Putri Rarasati; Moch. Yusuf Zen (Universitas Islam Balitar, 2019)
The background of this research limitations learning resources used in schools, which only use textbooks as well as the Student Worksheet. This led to insights on students' thinking is still lacking knowledge in the students over the implementation of PPKn material into everyday life is also lacking. Availability of learning resources in the school library are also less varied.This type of research is the research and development (Research and Development), adapting Sugiyono. The steps of this study are namely; pre-study observation, analysis of learners, format design, prototyping encyclopedia, validation validator to three experts, instructional simulation, then revision 2, analysis results, publications and complete. However, research conducted groove only to the revision of the results of validation, further trials instructional simulation Encyclopedia Archipelago in the Context of the Homeland, which aims to determine the students' responses. This is caused by the limited learning time refers to the curriculum.The end result can be seen product validationon an average of the three validators expert and gain a percentage of 607.7%. while the resultsinstructional simulation product testing to students showa positive response of 96.9%. and the response was negative 0.31%.This proves that the encyclopedia is very interesting, it is effective to use in learning PPKn.